Abnormal Excretion of Corticosteroid Sulphates in Patients with Breast Cancer. Issue 5849 (10th February 1973) - Ghosh, P. C.; Lockwood, E.; Pennington, G. W.
Abstract : In a preliminary study, the 24-hour urinary excretion of corticosteroid sulphates and free cortisol have been measured in a group of patients with breast cancer and compared with the excretion of the same compounds in a group of normal women of similar age. Excretion of corticosteroid sulphates in the breast cancer group was found to be markedly raised. In a small number of patients with localized cancer of sites other than the breast the level of corticosteroid sulphate was not raised. If proved metastases were present a noticeable rise was observed.